Measuring student-to-student confirmation in the college classroom: A Turkish adaptation and validation study - Kerimoglu, Esra; Alci, Bulent; Doenyas, Ceymi (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Students give attention, offer assistance, and acknowledge each other, thereby recognizing one another as valuable individuals and confirming one another. Given the importance of such student-to-student confirmation for academically and psychologically healthy classrooms, understanding student-to-student confirmation carries importance for the educational and personal well-being of students, and adaptation studies are needed to measure student-to-student confirmation in different groups. For this purpose, this study adapted the Student-to-Student Confirmation Scale to the Turkish context and language. For linguistic equivalence, both forward and backward translations were performed. The data obtained from the adapted version of the scale, which was tested on 648 Turkish undergraduate students (73.3% female, Mage = 20.95, range = 18 - 43), were analyzed using Confirmatory Factor Analysis (CFA). The adapted scale was found to have the same structure as its original one, which was tested on college students of various ethnicities at a large, public, Western university. By providing a valid and reliable scale in Turkish, this study enables the utilization of this scale in non-Western samples. This way, it has the potential to pave the way for cross-cultural comparisons as well as understanding and ameliorating this important concept in non-Western populations.
Keywords: Reliability; Scale adaptation; Student-to-student confirmation; Turkey; Validity; ITEM RESPONSE THEORY; TEACHER CONFIRMATION; FIT INDEXES; HIGHER-EDUCATION; CONNECTEDNESS; COMMUNICATION; PERCEPTIONS; REPLICATION; RAPPORT; Psychology; Social Sciences - Other Topics; Sociology